Increasing ecoliteracy and student creativity in waste utilization by usingmodels in project based learning social studies learning - Sekarsari Sunaryo Putri; Muhammad Japar; Riana Bagaskorowati (Institute of Advanced Engineering and Science, 2019)
This study aims to determine the increase in ecoliteracy and creativity in waste utilization by using a project-based-learning (PBL) model in social studies learning. This research is a classroom action research (Action Research). The design of the action model used is the Kemmis and Mc model. Taggart. This research was conducted in the fifth grade (V) of Primary Schools. Data collection techniques used in the study were observation sheet, interview, documentation, and field notes instruments. The results of this study showed that there was an increase in ecolithicacy ability.Based on the results of the pretest conducted on December 17, 2018, it can be seen that students in Telajung 02 Public Elementary School have not had the ability of Ecoliteracy and students' creativity in utilizing waste. Of the 32 students, the highest score that can be obtained is only 40 from a maximum score of 100. While the lowest value obtained is 20 from a maximum score of 100. In the first cycle, around 63% of students classified as having high ecoliteration ability, 9% classified as having the low ecoliteration ability and 28% classified as having the very low ecoliteration ability. In cycle II, there was an increase, around 90% of students classified as having high ecoliteration ability, 6% classified as having the low ecoliteration ability and 4% classified as having low ecoliteration ability. The average value of ecoliteration ability in the first cycle was 87.6 and the second cycle increased to 78.2. In addition, students become more active in the learning process and more courageous in expressing their opinions. This shows that the ecoliteracy and creativity of students can be improved through the project-based-learning model.